Numerically Bounded Linguistic Probability Schemes Are Unlikely to Communicate Uncertainty Effectively - D. R. Mandel; T. S. Wallsten; D. V. Budescu (Earth's Future, 2021)
Abstract In a recent issue of Earth's Future (vol. 7, pp. 1020–1026), S. C. Lewis et al. (2019, https://doi.org/10.1029/2019EF001273) recommended a numerically bounded linguistic probability (NBLP) scheme for communicating probabilistic information in extreme event attribution studies. We provide a critique of NBLP schemes in general and of Lewis et al.'s in particular, noting two key points. First, evidence from voluminous behavioral science research on the interpretation of linguistic probabilities indicates that NBLP schemes are an ineffective means of communicating uncertainty to others. Second, where the motivation to implement such schemes nevertheless persists, the schemes should be developed through an evidence‐based approach that seeks to optimize interpretational agreement between the scheme and users.